UK Top Banking Institutions: Executive Compensation and Company Performance - Mascoll, Kole (2011)
A well functioning financial system is a necessary prerequisite in a well functioning society. This view is extremely significant as it relates to the UK economy and society, in that the UK’s financial services sector contributes significantly to UK’s overall economic growth. UK banks play a vital role in an efficient and effective UK financial services industry. Therefore, it is important that researchers study, evaluate and measure the performance and performance related behaviours in this fraction of the financial services industry. Executive remunerative has and continues to be viewed by many as an essential component to the long-term growth and performance of the UK banking sector. Researchers and special interest groups have shared conflicting conclusions about the strength or significance of the relationship executive remuneration has to company performance. To examine this relationship this dissertation examined the annual reports of UK’s top banking institutions and compared the findings to the current literature in relation to executive compensation and company performance and other factors that may be relevant. The findings, even though contradictory, did give some invaluable insight into the relationship between executive compensation and company performance, corporate governance and its role, and differences in structure and design of various banking groups. In concluding this dissertation, the author believes that a relationship does exists between executive remuneration and company performance in UK’s top banks; however, more research and analysis would have to be applied in order to reveal its exact nature and significance.